Development and preliminary application of a quadruplex real-time PCR assay for differential detection of porcine circovirus 1–4 in Chengdu, China - Mi, Yong; Huang, Di; Zhuo, Yong; Li, Min; Yue, Jianguo; Zhong, Hongyu; Li, Huanhuan; Zhong, Zhijun; Liu, Haifeng; Peng, Guangneng; Zhu, Ling; Zhou, Xiaoxiao; et al. (Frontiers in Veterinary Science, 2024)
Porcine circovirus (PCV) typically causes severe immune suppression in pigs, leading to mixed clinical infections with various pathogens that can cause significant harm to the pig industry. PCV has four subgenotypes, with PCV4 being an emerging virus that requires investigation due to its potential for epidemic outbreaks. Therefore, there is a need to develop a method that can detect all four PCV strains simultaneously. In this study, four pairs of specific primers and TaqMan probes were designed based on the conserved sequence of the PCV1-4 ORF2 gene to establish a PCV1-4 TaqMan multiplex realtime quantitative PCR method. The novel method was compared to six commercial testing kits for its efficacy. Then, a total of 595 mixed samples of spleen and lymph node collected from 12 districts in Chengdu from July to December 2021 were tested using the novel method. The results showed that the novel PCV1-4 TaqMan multiplex real-time quantitative PCR detection method has satisfied specificity, sensitivity, and repeatability. The positive rates of PCV1, PCV2, and PCV3 in Chengdu were 2.18%, 31.60%, and 15.29%, respectively, while no positive PCV4 was detected. The mixed infection rate of PCV2 and PCV3 was 5.21%. Our novel method may be as a potential method for PCV1-4 detection. Currently, PCV2 is the main epidemic PCV subtype in Chengdu, while the potential threat of PCV4 should also be considered.